POSITIONING POLITIK KAMPANYE PEMILIHAN PRESIDEN 2014 DALAM IKLAN VIDEO MUSIK YOUTUBE - Nahrul Hayat; Hasrullah Hasrullah (KAREBA : Jurnal Ilmu Komunikasi, 2016)
The study aims to reveal representation of meaning of the Indonesia's presidential election campaign in 2014 within the Youtube music video advertisement; and explain the construction of political positioning in the advertisement. The study method used is descriptive qualitative research method through direct observation of the object and the study of literature. The data were analyzed by using semiotic analysis of Roland Barthes which consists of two signification level, namely first level of signification (denotation level) and the second level of signification (connotation level). Primary data consists of verbal text and non-verbal text (visual) of the music video. Secondary data consists of books and related documents. The results showed that the main connotative meaning contained in the music video advertisement of presidential election campaign 2014 is that each pair of candidates is the best and most worthy partner to lead Indonesia. The results of the analysis of the connotative sign also found that the construction of political positioning of Prabowo is a presidential candidate who has a decisive and courageous self-image as well as respected and honored candidate;possess military background and has a formal –procedural leadership style; and has militaristic nationalism ideology. As the opposite, Jokowi’s political positioning construction is a presidential candidate who has particularly honest and populist self-image as well as liked and favored; possess civilian background with informal-spontanious leadership style; and has the dominant ideology of democratic socialism.  Penelitian ini bertujuan untuk mengungkap representasi makna yang ada dalam iklan video musik Youtube kampanye pemilihan presiden Indonesia 2014; dan menjelaskan konstruksi positioning politik dalam iklan tersebut. Metode yang digunakan adalah metode penelitian deskriptif kualitatif melalui pengamatan langsung terhadap objek dan kajian pustaka. Data dianalisis dengan menggunakan analisis semiotika Roland Barthes yang terdri dari dua tingkat sistim penandaaan, yakni penanndaan tingkat pertama (level denotasi) dan penandaan tingkat kedua (level konotasi). Data primer terdiri dari teks verbal dan non-verbal (visual) video musik. Data sekunder terdiri dari buku dan dokumen terkait. Hasil penelitian menunjukkan bahwa secara konotatif makna utama yang terkandung dalam iklan video musik kampanye pemilihan presiden 2014 adalah bahwa masing- masing pasangan kandidat merupakan pasangan terbaik dan paling layak untuk memimpin Indonesia. Hasil analisis tanda konotatif juga menemukan bahwa konstruksi positioning politik Prabowo adalah sebagai calon presiden yang memiliki citra diri tegas dan pemberani serta disegani dan disukai; berlatar belakang militer dan memiliki gaya memimpin yang formal-prosedural; serta berideologi nasionalisme-militeristik. Sebaliknya konstruksi positioning politik Jokowi adalah sebagai calon presiden yang meiliki citra diri jujur dan merakyat serta disenangi dan disukai; berlatar belakang sipil dengan gaya memimpin yang informal-spontanious; serta memilki ideologi dominan sosialisme-demokratis.